Clay supported TiO2 nanoparticles for photocatalytic degradation of environmental pollutants: A review. Issue 5 (October 2018) - Mishra, Amit; Mehta, Akansha; Basu, Soumen
Abstract: Pure air and water are essential requirements for sustainability of human civilization and wildlife on earth. However, due to illicit industrial practices of waste disposal, the presence of harmful effluents has increased in both air and water bodies which are harmful to both humans and wildlife. Heterogeneous photocatalysis can be a promising measure for the removal of these pollutants from both water and air. TiO2 is a highly investigated photocatalyst for such a purpose but it suffers from few demerits which hamper its practical application. Commercially available TiO2 (Degussa P25) has low photocatalytic efficiency owing to its low surface area (50 m 2 /g) and porosity and it is difficult to separate it from the reaction mixture which makes it less reusable. In order to overcome these limitations a variety of materials have been used as catalytic supports for TiO2 . Among these clays have gained immense attention since they are cheap, highly available in the earth's crust and possess thermal, chemical and mechanical stability. Clays provide TiO2 with the high surface area, porosity, high number of surface active sites which makes TiO2 /clay nanocomposites highly active photocatalyst than pure TiO2 . The review represents different methodologies for TiO2 /clay synthesis and the impact of clay on the physical and photocatalytic activity of TiO2 . Also, the role of different clay supports for TiO2 and comparison of their effect on the photocatalytic activity of TiO2 has been covered.